Multi-Resolution Method Based on Riemann Solvers for Detonation and Deflagration in High Dimension (Communications in Computational Physics, 2021)
In this paper, we propose accurate Riemann solvers for detonation and deflagration with sharp interface in high dimension. The standard finite volume schemeis used for each fluid away from material interface, the detonation and the deflagration interfaces are captured by the level set method, small cut cells are treated witha mixing procedure to get stable algorithm. By Riemann solver for the detonationand the deflagration, the interface fluxes are obtained. With the help of the adaptivemulti-resolution algorithms, we extend the method to three dimension conveniently.Numerical examples in two or three-dimension are carried out to demonstrate the potential and robustness of the method.